Molecular Epidemiology and Virulence Profiles of Colistin-Resistant Klebsiella pneumoniae Blood Isolates From the Hospital Agency “Ospedale dei Colli,” Naples, Italy - Esposito, Eliana P.; Cervoni, Matteo; Bernardo, Mariano; Crivaro, Valeria; Cuccurullo, Susanna; Imperi, Francesco; Zarrilli, Raffaele (Frontiers in Microbiology, 2018)
Resistance to colistin is increasingly reported in Klebsiella pneumoniae clinical isolates. The aim of this study was to analyze the molecular epidemiology and virulence profiles of 25 colistin-resistant Klebsiella pneumoniae blood isolates from the Hospital Agency “Ospedale dei Colli”, Naples, Italy, during 2015 and 2016. Colistin MIC values of isolates ranged from 4 to 256 mg/L. The inactivation of the mgrB gene, encoding a negative regulator of the PhoQ/PhoP signaling system, was the most frequent mechanism of colistin resistance found in 22 out of 25 isolates. Of these, 10 isolates assigned to ST512 and PFGE types A and A4 showed identical frameshift mutation and premature termination of mgrB gene; 4 isolates assigned to ST258 and PFGE types A1 showed non-sense, frameshift mutation and premature termination; 3 and 1 isolates assigned to ST258 and PFGE A2 and ST512 and PFGE A3, respectively, had insertional inactivation of mgrB gene due to IS5-like mobile element; 2 isolates assigned to ST101 and 1 to ST392 had missense mutations in the mgrB gene, 1 isolate assigned to ST45 showed insertional inactivation of mgrB gene due to IS903-like mobile element. phoQ missense mutations were found in 2 isolates assigned to ST629 and ST101, respectively, which also showed a missense mutation in pmrA gene. The mcr-1-2-3-4 genes were not detected in any isolate. Colistin-resistant K. pneumoniae isolates showed variable virulence profiles in Galleria mellonella infection assays, with the infectivity of two isolates assigned to ST45 and ST629 being significantly higher than that of all other strains (P<0.001). Interestingly, colistin MIC values proved to make a significant contribution at predicting lethal doses values (LD50 and LD90) of studied isolates in G. mellonella. Our data show that MgrB inactivation is a common mechanism of colistin resistance among K. pneumoniae in our clinical setting. The presence of identical mutations/insertions in isolates of the same ST and PFGE profile suggests the occurrence of clonal expansion and cross-transmission. Although virulence profiles differ among isolates irrespective of their genotypes, our results suggest that high colistin MIC could predict lower infectivity capability of the isolates.